Cytidine Triphosphate Synthase Four From Arabidopsis thaliana Attenuates Drought Stress Effects - Krämer, Moritz; Dörfer, Eva; Hickl, Daniel; Bellin, Leo; Scherer, Vanessa; Möhlmann, Torsten (Frontiers in Plant Science, 2022)
CTP synthase catalyses the final step in pyrimidine de novo synthesis. In Arabidopsis, this protein family consists of five members (CTPS1-5) and all of them localize to the cytosol. Specifically, CTPS4 expression shows a massive upregulation of transcript levels during abiotic stress, in line with increased staining of CTPS4 promoter activity in hypocotyl, root and to lesser extend leaf tissues upon stress application. In a setup to study progressive drought stress, CTPS4 knockout mutants accumulated less fresh and dry weight at day 5-7 and showed impaired ability to recover from this stress after three days rewatering. Surprisingly, a thorough physiological characterization of corresponding plants only revealed alterations in assimilation and accumulation of soluble sugars including those related to drought stress in the mutant. Bimolecular fluorescence complementation (BIFC) studies indicated interaction of CTPS4 with other isoforms, possibly affecting cytoophidia (filaments formed by CTP synthases) formation. Although the function of these structures has not been thoroughly investigated in plants, altered enzyme activity and effects on cell structure are reported in other organisms. CTPS activity is required for cell cycle progression and growth. Furthermore, drought can lead to accumulation of ROS and by this to DNA damage. We hypothesize that effects on cell cycle or DNA repair might be relevant for the observed impaired reduced drought stress tolerance of CTPS4 mutants.